Protein S Regulates Neural Stem Cell Quiescence and Neurogenesis. (8th November 2016) - Zelentsova, Katya; Talmi, Ziv; Abboud‐Jarrous, Ghada; Sapir, Tamar; Capucha, Tal; Nassar, Maria; Burstyn‐Cohen, Tal
Abstract : Neurons are continuously produced in brains of adult mammalian organisms throughout life—a process tightly regulated to ensure a balanced homeostasis. In the adult brain, quiescent Neural Stem Cells (NSCs) residing in distinct niches engage in proliferation, to self‐renew and to give rise to differentiated neurons and astrocytes. The mechanisms governing the intricate regulation of NSC quiescence and neuronal differentiation are not completely understood. Here, we report the expression of Protein S (PROS1) in adult NSCs, and show that genetic ablation of Pros1 in neural progenitors increased hippocampal NSC proliferation by 47%. We show that PROS1 regulates the balance of NSC quiescence and proliferation, also affecting daughter cell fate. We identified the PROS1‐dependent downregulation of Notch1 signaling to correlate with NSC exit from quiescence. Notch1 and Hes5 mRNA levels were rescued by reintroducing Pros1 into NCS or by supplementation with purified PROS1, suggesting the regulation of Notch pathway by PROS1. Although Pros1 ‐ablated NSCs show multilineage differentiation, we observed a 36% decrease in neurogenesis, coupled with a similar increase in astrogenesis, suggesting PROS1 is instructive for neurogenesis, and plays a role in fate determination, also seen in aged mice. Rescue experiments indicate PROS1 is secreted by NSCs and functions by a NSC‐endogenous mechanism. Our study identifies a duple role for PROS1 in stem‐cell quiescence and as a pro‐neurogenic factor, and highlights a unique segregation of increased stem cell proliferation from enhanced neuronal differentiation, providing important insight into the regulation and control of NSC quiescence and differentiation. Stem Cells 2017;35:679–693 Abstract : This study identifies Protein S (PROS1) as a pleiotropic regulator of neural stem cell (NSC) biology. PROS1 expressed by NSCs regulates the balance between NSC quiescence as well as daughter cell fate determination. PROS1 affects the NSC quiescence/proliferation choice point through Notch1 signaling. Zelentsova et al. demonstrate that Notch signaling in NSCs is responsive to PROS1 at the transcriptional level. Loss of PROS1 in NSCs leads to decreased Notch1 signaling, with increased NSC proliferation, which surprisingly persists in aged mice. Additionally, the authors show that PROS1 is instructive for neurogenesis over gliogenesis, and reveal a unique uncoupling between NSC proliferation and increased neurogenesis.